Incidence and risk factors of acute kidney injury in redo cardiac surgery: a single center analysis - Luca Salvatore De Santo; Antonino Salvatore Rubino; Antonio Pio Montella; Caterina Golini Petrarcone; Lucrezia Palmieri; Denise Galbiati; Antonio Pisano; Marisa De Feo (Scientific Reports)
Abstract The incidence, risk factors and prognostic implications of acute kidney injury (AKI) in patients undergoing redo cardiac surgery are still poorly defined. We prospectively collected data on 394 consecutive redo patients between January 2011 and October 2020. Patients were divided into groups according to the occurrence of different degrees of postoperative AKI (No AKI vs. Any AKI; No AKI-AKI 1 vs. AKI 2–3). The relationship between AKI and other major complications was also investigated. Postoperatively, AKI 1 occurred in 124 (31.5%), AKI 2 in 36 (9.1%) and AKI 3 in 64 (16.2%). Higher KDIGO classes were associated with increased in-hospital mortality: 5.3% among patients with no postoperative AKI and 8.9%, 13.9% and 64.1% in patients with AKI 1, 2 and 3, respectively (p < 0.001). Age, baseline hemoglobin, comorbidity, EuroSCORE II, operative time and transfusion during CPB proved to be significantly associated to the occurrence of AKI. Our study confirms the burden and prognostic role of AKI in a large, all comers, single center database of redo cardiac procedures.